In vitro study of effectivity of bacteriophages in the prevention and degradation of biofilms formed by uropathogenic E. Coli in urinary chatheters - Wilson, Marc-Michel (My University, 2018)
As the primary mode of growth of bacterial populations biofilms are a major contributing factor to the globally pertinent issue of antibiotic -resistant infections. Research into the use of bacteriophages to combat bacterial infections was abandoned by most of the world following the discovery of antibiotics and, only recently, in light of the imminent threat to global health that is associated with antimicrobial resistance (AMR), has this alternative started to garner renewed interest on an international scale. This study is aimed at furthering specific understanding in this newly resurgent field, by investigating interactions between bacteriophages and the biofilms that are prevalent in E. coli urinary tract infections (UTIs). The study involved isolation of bacteriophages from the environment and scrutiny of their capacity to both degrade existing, and prevent the formation of, uropathogenic Escherichia coli (UPEC) biofilms, in vitro in urinary catheters. Techniques employed to this end included: multifaceted microbial and viral culture, isolation, and characterization; PCR and DNA sequencing; transmission electron microscopy (TEM); spectrophotometry; and flow cytometry. Isolation and characterization of two biofilm forming uropathogenic E. coli strains (UEmw_8 and UEmw_9) were carried out and identification was confirmed morphologically, biochemically, and genetically (using 16S rRNA gene sequencing). The isolation, purification, and description of two novel lytic bacteriophages (vB_EcoP-U8, and vB_EcoX-U9) that are active, with high specificity, against the clinical E. coli strains was achieved. The genome of bacteriophage vB_EcoP-U8 has been fully sequenced and annotated. Both bacteriophages were capable of significantly reducing established biofilms formed by their respective bacterial hosts (UEmw_8 and UEmw_9) in catheters in vitro. Pre-treatment of catheters with bacteriophage was ineffective in preventing formation of biofilms of either bacterial strain in the catheters over a 24 hour period. Future studies should focus on the specific mechanisms of action of these bacteriophages, with the ultimate goal of creating prevention strategies or treatments for E. coli–associated UTIs.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Medicine